The LuxS/AI-2 Quorum-Sensing System of Streptococcus pneumoniae Is Required to Cause Disease, and to Regulate Virulence- and Metabolism-Related Genes in a Rat Model of Middle Ear Infection - Yadav, Mukesh K.; Vidal, Jorge E.; Go, Yoon Y.; Kim, Shin H.; Chae, Sung-Won; Song, Jae-Jun (Frontiers in Cellular and Infection Microbiology, 2018)
Objective:Streptococcus pneumoniae colonizes the nasopharynx of children, and from nasopharynx it could migrate to the middle ear and causes acute otitis media (AOM). During colonization and AOM, the pneumococcus forms biofilms. In vitro biofilm formation requires a functional LuxS/AI-2 quorum-sensing system. We investigated the role of LuxS/AI-2 signaling in pneumococcal middle ear infection, and identified the genes that are regulated by LuxS/AI-2 during pneumococcal biofilm formation. Methods:Streptococcus pneumoniae D39 wild-type and an isogenic D39ΔluxS strain were utilized to evaluate in vitro biofilm formation, and in vivo colonization and epithelial damage using a microtiter plate assay and a rat model of pneumococcal middle ear infection, respectively. Biofilm structures and colonization and epithelial damage were evaluated at the ultrastructural level by scanning electron microscopy and confocal microscopy. Microarrays were used to investigate the global genes that were regulated by LuxS/AI-2 during biofilm formation. Results: The biofilm biomass and density of D39ΔluxS were significantly (p < 0.05) lower than those of D39 wild-type. SEM and confocal microscopy revealed that D39ΔluxS formed thin biofilms in vitro compared with D39 wild-type. The in vivo model of middle ear infection showed that D39ΔluxS resulted in ~60% less (p < 0.05) bacterial colonization than the wild-type. SEM analysis of the rat middle ears revealed dense biofilm-like cell debris deposited on the cilia in wild-type D39-infected rats. However, little cell debris was deposited in the middle ears of the D39ΔluxS-inoculated rats, and the cilia were visible. cDNA-microarray analysis revealed 117 differentially expressed genes in D39ΔluxS compared with D39 wild-type. Among the 66 genes encoding putative proteins and previously characterized proteins, 60 were significantly downregulated, whereas 6 were upregulated. Functional annotation revealed that genes involved in DNA replication and repair, ATP synthesis, capsule biosynthesis, cell division, the cell cycle, signal transduction, transcription regulation, competence, virulence, and carbohydrate metabolism were downregulated in the absence of LuxS/AI-2. Conclusion: The S. pneumoniae LuxS/AI-2 quorum-sensing system is necessary for biofilm formation and the colonization of the ear epithelium, and caused middle ear infection in the rat model. LuxS/AI-2 regulates the expression of the genes involved in virulence and bacterial fitness during pneumococcal biofilm formation.